Pengaruh Keyakinan Diri Terhadap Kualitas Hidup Wanita Perimenopause Di Desa Kembangan, Kecamatan Sukomoro, Kabupaten Magetan - sausan hanifah; Purwanto Triana Septianti; Handayani Tinuk Esti; Wisnu Nurwening Tyas (Midwifery Care Journal, 2026)
Menopause is a physiological phase marked by the cessation of ovarian function and a decrease in estrogen, which affects a woman’s physical, psychological, and social condition. An important factor in facing this is self-confidence, which helps women adapt and maintain their quality of life. This study aimed to find out the influence of self-confidence on the quality of life of perimenopausal women in Kembangan Village, Sukomoro District, Magetan Regency. The design was correlational with a cross-sectional approach on 100 women aged 45–49 years using simple random sampling. Data collection was conducted using the General Self-Efficacy Scale (GSES) questionnaire to measure self-confidence and the Menopause-Specific Quality of Life (MENQOL) to measure quality of life, questionnaires and analyzed with the Chi-Square test at a significance level of α = 0.05. The results showed that most respondents had high self-confidence (88%) and good quality of life (93%). Women with high self-confidence had a good quality of life of 95.5%, while the low self-confidence group was 75.0%. The Chi-Square test showed p = 0.036 (p < 0.05), which proves that there is a significant effect of self-confidence on the quality of life of perimenopausal women. In conclusion, the higher the self-confidence, the better their quality of life, so health education and psychological support are needed to improve it